Construction and practice of the teaching evaluation system for the undergraduate major of New Media Technology - Guo, Yanling (Pacific International Journal, 2024)
This study explores the construction and practical implementation of a teaching evaluation system tailored for the undergraduate major of New Media Technology. Rooted in literature advocating for formative assessments and critical thinking skills, the research endeavors to fill this void with a bespoke 360-degree comprehensive evaluation mechanism. Drawing on principles of objectivity, comprehensiveness, adaptability, and developmental focus, the study proposes a system encompassing self-evaluation, peer evaluation, student evaluation, and third-party evaluation. Beyond its immediate application in New Media Technology, the study emphasizes the broader implications of its findings for emerging interdisciplinary majors, aiming to contribute to national strategies for scientific and technological innovation. The study unfolds in the context of the New Media Technology major at Qilu University of Technology, offering specific insights into curriculum features, talent cultivation objectives, and industry requisites. Following a detailed exploration of evaluation principles, content, and methods, the study presents the results of the newly implemented system, revealing nuanced strengths and areas for improvement. These findings culminate in a set of recommendations aimed at continuous system review, enhanced collaborative engagement, increased practical application in instructional design, strategic resource allocation, industry integration, and comprehensive student support services. The conclusion reflects on the study's contribution to refining teaching evaluation systems, fostering ongoing improvements, and nurturing the next generation of talents in the ever-evolving landscape of new media technology.